Relation between disorder premenstrual disforic and anxiety, depression and stress in university students of the UNMSM - Riveros Q., Marcelino (2009)
In this investigation we used the rating scale Stress (EVES), built and validated by Laura B. Sapia of gold and Neifert, Ivana; Likerts is a scale consisting of 22 items. Be applied to a sample of 352 subjects of both sexes in the province of Entre Rios. Getting a Cronbach alpha of 0.86 for the full scale.